Myocardial repolarization is affected in patients with diabetic retinopathy - Coşgun, Mehmet; Sincer, İsa; Erdoğdu, Tayfur; Dişikirik, Tuğba; Güneş, Yılmaz; Kurtar Mansıroğlu, Aslı; Erdal, Emrah; Topuz, Mustafa (Journal of Surgery and Medicine, 2021)
Background/Aim: Diabetes Mellitus (DM), considered the equivalent of coronary artery disease, is one cause of ventricular repolarization (VR) dispersion. Retinopathy is one of the vascular consequences of diabetes. The association between myocardial repolarization dispersion and diabetic retinopathy is not fully elucidated. We aimed to evaluate ventricular repolarization using Tp-e interval and corrected (c) Tp-e/QT ratio in DM patients with and without retinopathy. Methods: A total of 124 diabetic subjects were included in this retrospective cohort study. All medical data were obtained from the electronic database of our university hospital. The subjects were divided into the no diabetic retinopathy (NDR) group (n=45), and the diabetic retinopathy (DR) group (n=79), which were compared in terms of demographic features, clinic and laboratory findings, and electrocardiographic findings such as QT, QTc, Tp-e, Tp-e/QT, Tp-e/QTc. Results: The groups were similar in terms of demographic features (P>0.05). Both Tp-e interval and Tp-e/QTc were significantly prolonged in the DR group compared to the NDR group. There were significant correlations between Tp-e, Tp-e/QTc, DM duration, and age. In multivariate logistic regression analysis, Tp-e (OR=6.01, %95 CI=4.17-7.52, P=0.012), Tp-e/QTc (OR=1.215, 95% CI=0.874-1.612, P=0.029), and DM duration (OR=1.422, 95% CI= 1.146–1.712, P<0.001) were independent predictors of DR. Conclusion: We showed that DM patients with retinopathy may also have an increased risk for sudden cardiac death due to ventricular arrhythmogenesis.